(untitled) (@limentech, Ciencia y Tecnología Alimentaria, 2015)
Pectin is a thickening agent used in the food and pharmaceutical industries due to its gelling properties. The objective of this article is to present the results of a study aimed at extracting and characterizing pectin from Tahiti lemon peel at two stages of ripeness. Extraction of green and ripe Tahiti lemon peel was carried out by acid hydrolysis with HCl at different pH, temperatures, and times. In the case of green Tahiti lemon peel, the ideal extraction conditions in relation to the percentage yield were 1.26%, pH 2.5, 45 minutes, and 100°C. For ripe Tahiti lemon peel, these conditions were 0.90%, pH 2.0, 75 minutes, and 90°C. The resulting pectin was evaluated for moisture content, ash, methoxyl, free acidity, equivalent weight and degree of esterification, applying an analysis by infrared spectroscopy. The results of the characterization of green and ripe lemon were: 5.4% and 3.2% ash respectively; 14.0% and 8.2% moisture; 84.2% and 91.6% anhydrogalacturonic acid; 94.5% and 90.7% esterification percentage; 14.0% and 14.6% methoxyl index. It is concluded that pectin has a high percentage of esterification, compared to commercial pectin (76%), so it is recognized as high methoxyl, and is considered suitable for use in the industry, due to its ease of gelation.